(untitled) (The Conference Hub, 2025)
Like many other linguistic units, phraseological units containing food products in English have been applied to various researches. However, little research has been done to explore linguocultural specificity of food idioms in the English and Uzbek languages. This paper, based on comparative analysis, discusses the importance of food idioms in reflecting the national and cultural identity of the nation. The research findings indicate that the formation of phraseological units in each nation depends on national world picture of each nation, so the same concept might be expressed using different idioms in two studied languages. The article analyzes English idiomatic units using their equivalents in Uzbek and demonstrates idioms reflecting the nation’s worldview and cultural identity. Based on this study we argue that more research is needed to investigate culturally marked food idioms in both languages.